Study of menstrual disorders and its correlation with BMI in adolescents - Agrawal, Megha; Goyal, Ashish; Gupta, Priyanka; Agrawal, Anshul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Due to change in lifestyle, habits, diet, the prevalence of obesity has increased. Excess weight and obesity are associated with irregular menstrual cycles, which reduce fertility and increase hormone-sensitive cancers. Obesity is considered to cause abnormality of sex steroid hormone balance. Irregular menstruation is more frequently observed in women who became obese during puberty than in those who were obese during infancy. Obesity has a strong association with infertility and menstrual irregularities. Methods: This cross-sectional study was conducted at Durgapur (West Bengal), where total 600 adolescent girls aged 12-17 years from DAV Model School, Durgapur and GMPS High School, Durgapur were selected. Results: Out of total 600 girls, 119 girls (19.8%) had BMI<18.5 kg/m2, 357 girls (59.5%) had BMI between 18.5-24.99 kg/m2 and 124 girls (20.7%) had BMI>25 kg/m2. Only 68 girls (57.1%) with less BMI, 205 girls (57.4%) with normal BMI and 62 girls (50%) with BMI>25 kg/m2 had dysmenorrhoea. Only 19 girls (16%) with less BMI, 46 girls (12.9%) with normal BMI and only 15 girls (12.1%) with higher BMI had menorrhagia. Only 4 girls (3.4%) with less BMI, 14 girls (3.9%) with normal BMI and 12 girls (9.7%) with high BMI had hypomenorrhoea. Only 10 girls (8.4%) with less BMI, 37 girls (10.4%) with normal BMI and only 28 girls (22.5%) with high BMI had irregular cycles. Only 5 girls (4.2%) with less BMI, 12 girls (3.4%) with normal BMI and only 11 girls (8.9%) with high BMI had oligomenorrhoea. Only 2 girls (1.7%) with less BMI, 3 girls (0.8%) with normal BMI and only 4 girls (3.2%) with higher BMI had polymenorrhoea. Only 43 underweight girls (36.1%), 166 girls (46.5%) with normal BMI and 68 girls (54.8%) with higher BMI had premenstrual symptoms. Conclusions: Mean BMI was found 21.6±3.64 kg/m2. High BMI girls had more oligomenorrhoea, hypomenorrhoea, irregular menstrual cycles, polymenorrhoea, premenstrual symptoms and less dysmenorrhea and menorrhagia comparatively to normal BMI girls and underweight girls.